ZOOPLANKTON DYNAMICS AND DIVERSITY IN WATER OF ABANDONED POND ECOSYSTEMS DURING PRE-COVID-19 AND POST-COVID-19 PERIOD - NASEER, BUSHRA; SINHA, SHAILENDRA KUMAR (The Bioscan, 2023)
Zooplankton community of two abandoned ponds have been analysed and compared between pre-COVID-19 and post-COVID-19. Results showed that the water quality improved during the post-COVID-19 period as compared to the pre-COVID-19 period (PRC91/POC19) in terms of physicochemical parameters with the annual average values for pond 1 as DO (in mg/L) 4.6/4.94, pH 6.58/7.18, TDS (in mg/L) 1103.25/592.91, PO43- (in mg/ L) 0.69/0.61; and for Pond 2 as DO (in mg/L) 4.45/5.46, pH 7.55/7.71, TDS (in mg/L) 920.91/381.58, PO43- (in mg/L) 0.41/0.29. Zooplankton community was found less diversified in the POC19 but stable. Zooplankton population showed rotifers as the dominant group during both the periods.